ANALISIS PERILAKU PENYIMPANAN DAN PEMBUANGAN OBAT MASYARAKAT RW 18 KELURAHAN DUREN JAYA BEKASI - Azis, Muhammad Fikry; Rohenti, Iin Ruliana; Maratun Shoaliha (JIFI (Jurnal Ilmiah Farmasi Imelda), 2023)
Storage and disposal of drugs is an activity to manage medicines at home. This has become a worldwide concern, because in everyday behavior it is found that storage and disposal are still carried out inappropriately. The lack of community willingness to do this creates problems that will arise in the future. This study aims to determine the behavior of storing and disposing of drugs in RW 18 Duren Jaya Village, East Bekasi. Methods: This study used an analytical survey research method, namely a cross sectional survey. Sampling was carried out in a non-random way, namely purposive sampling technique with inclusion criteria aged 17-55 years and had been storing and disposing of drugs. 95 respondents participated in this study. The results showed that 52 respondents (55%) had unused or expired drugs. Among them have received information about how to dispose of drugs as much as 63%. In addition, almost all respondents received information about drug storage as much as 75%. In the analysis of the level of drug storage behavior, it was found that 92 respondents (96.8%) behaved well and the analysis of the level of drug disposal behavior found that 62 respondents (65.3%) behaved fairly. The conclusion shows that drug storage has been carried out properly while disposal behavior is still lacking, so further socialization is needed regarding good household pharmaceutical waste management.